2006
DOI: 10.1021/om0607447
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Design for the Assembly of Polynuclear Complexes:  Syntheses and Structures of Trinuclear and Tetranuclear Aluminum Alkyl Complexes Bearing Tripodal Diamidoselenophosphinito Ligands and a Comparison to Related Tripodal Triamidophosphine Complexes

Abstract: Reactions of the triaminophosphines P(CH2NHArR)3 (1a−c, where ArR = 3,5-(CF3)2C6H3 for a; ArR = Ph for b, ArR = 3,5-Me2C6H3 for c) with selenium afford the triaminophosphine selenides SeP(CH2NHArR)3 (2a−c). The phosphine selenides 2a−c react with 4 equiv of AlMe3 at room temperature to generate the triangular trinuclear aluminum complexes [P(CH2NArR)2Se](AlMe2)3 (3a−c). The byproduct of the formation of 3a was hydrolyzed and provided CH3CH2N(H)-3,5-(CF3)2C6H3. When 2a−c are treated with excess AlMe3, the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…The Cu-Se distance is 2.3505(7) A ˚slightly longer than 2.342(1)-2.343( 9 The P-Se bond distances in compound 6, 2.1707 (19) A ˚are slightly shorter than that of compound 5 [2.1781(16) A ˚] which is reflected from their P-Se coupling constants in 31 P NMR: 598 Hz in 6 and 568 Hz in 5. The Se-P-Fe angles in the compound 6, 113.84 (8) • , are different to those of 121.71(7) • observed in 5.…”
Section: Structural Descriptionscontrasting
confidence: 66%
See 1 more Smart Citation
“…The Cu-Se distance is 2.3505(7) A ˚slightly longer than 2.342(1)-2.343( 9 The P-Se bond distances in compound 6, 2.1707 (19) A ˚are slightly shorter than that of compound 5 [2.1781(16) A ˚] which is reflected from their P-Se coupling constants in 31 P NMR: 598 Hz in 6 and 568 Hz in 5. The Se-P-Fe angles in the compound 6, 113.84 (8) • , are different to those of 121.71(7) • observed in 5.…”
Section: Structural Descriptionscontrasting
confidence: 66%
“…In addition, the bridging selenophosphinito (R 2 PSe − ) unit was also revealed in a tetranuclear Al III complex synthesized by Johnson and Han. 8 Recently, Rothenberger et al reported the generation of P-Se anions by breakage of the neutral group 15/16 ligand (Woollins reagent), which ultimately bridged copper via selenium and phosphorus atoms of the [(-O)(R)PSe] 2 2− unit to form cluster compounds. 9 In a search for heterometallic complexes containing a P-Se fragment where both P and Se atoms bridged metal centers; surprisingly, no single molecule with organoselenophosphorus ligands has been structurally characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The IR stretching frequencies and chemical shifts of the 31 P NMR resonances of all complexes are reported in 3 . [29][30][31][32] The shift of the 31 P{ 1 H} NMR signal of 6, which is a classical coordination shift, is 15 ppm to a lower field.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported the synthesis and initial study of the tripodal amido phosphane ligands of the type P(CH 2 NHAr R ) 3 [11][12][13] where Ar R is an aryl substituent. With metals in oxidation states greater than +3, these ligands preferentially form complexes where all three amido donors chelate to the metal, similar to other tripodal amido ligands.…”
Section: Introductionmentioning
confidence: 99%